Probing entry inhibitors' activity on HIV and development of new fusion inhibitors : integrating evolutionary biology with virology - Borrego, Pedro José Vieira Borga Martins, 1980- (2011)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2011